Factors Influencing the Dissemination of Tweets at the American College of Surgeons Clinical Congress 2018. Issue 4 (April 2021) - Sharp, Stephen P.; Mackenzie, Douglas G.; Ong, David S.Y.; Mountziaris, Paschalia M.; Logghe, Heather J.; Ferrada, Paula; Wexner, Steven D.
Background: Social media is increasingly used in surgery, facilitating the dissemination of knowledge. Social media can potentially aid networking, education, and information exchange. This study explored the impact of tweet components and tweeter characteristics during a large surgical congress to inform recommendations for optimizing social media use at future surgical conferences. Methods: Twitter activity was monitored during the American College of Surgeons Clinical Congress 2018 using NodeXL to extract tweets containing the conference hashtag #ACSCC18 (or #ACSCC2018). Multivariable logistic regression analysis was performed to identify independent predictors of retweet activity, also testing for multicollinearity and interactions among variables. Results: There were 4386 tweets that contained #ACSCC18 (or #ACSCC2018) posted from 1023 Twitter accounts. A larger group of Twitter accounts just retweeted. Other Twitter accounts with a stake in the conference neither tweeted nor retweeted. In a multivariable analysis of original tweets, the following were all independently associated with retweets, in decreasing order of effect size: mention of other tweeters, multimedia, inclusion of other hashtags, and the number of followers. In contrast with other conferences, the inclusion of a weblink (URL)—for example, link to paper or blog—was not associated with retweets. Discussion: This study helps understand social media impact at surgical conferences. Engage by tweeting and retweeting. Mention other tweeters, add multimedia, include congress hashtags and topic-specific hashtags, and build your followers. Although not associated with retweet activity in this study, the inclusion of URLs can still contribute in substantiating the disseminated content based on findings at other conferences.